Penyetaraan Jabatan Administrasi ke dalam Jabatan Fungsional Bagi Aparatur Sipil Negara Perspektif Fiqh Siyasah - Liza Yuliana; John Kenedi; Ismail Jalili (Journal of Sharia and Legal Science, 2024)
The purpose of this study is to examine the problem of equalizing administrative positions into functional positions for state civil servants at the State Islamic University of Bengkulu from the perspective of "fiqh siyasah" according to the regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 17 of 2021 concerning the equalization of administrative positions into functional positions. The type of research is Field Research, namely Qualitative Research. The data collection technique for this research uses questionnaires, interviews and documentation. The data analysis technique goes through three stages, namely Reduction, data presentation and drawing conclusions. The conclusion of this study is that the Implementation of Permanpan RB Number 17 of 2021 concerning the Equivalence of Administration to Functional Positions within the State Islamic University of Bengkulu, is in line with Islamic Principles Viewed from the perspective of: The Principle of Power as a Mandate As a State Civil Apparatus who is entrusted to lead an Institution in this case the Fatmawati State Islamic University of Bengkulu, which is led by a Chancellor, has carried out his duties to implement the Ideals of Bureaucratic Reform, namely implementing Permenpan RB Number 17 of 2021, Bureaucratic Reform, Concerning the Equivalence of Administrative Positions to Functional Positions within the Fatmawati State Islamic University of Bengkulu.